(untitled) (Bangladesh Journal of Botany, 2026)
Kalanchoe contains various bioactive compounds. Qualitative phytochemical screening of five species revealed strong, moderate, weak response to ethanol, methanol, and aqueous solvent extracts respectively. Ethanol extracts exhibited the highest antioxidant activity with K. pinnata (IC50 = 25.29 µg/ml). Total phenolic contents (TPC)) was highest in ethanol extracts of K. pinnata (154.82mg GAE/g). The LC50 conducted by brine shrimp lethality bioassay exhibited stronger cytotoxic activity in K. pinnata with LC50 = 64.44 µg/ml. The study also highlights the comparative presence of different phytochemicals, TPC, DPPH, and cytotoxic activity which will be helpful for phytochemical and pharmacological analysis in future. Bangladesh J. Bot. 55(1): 173-180, 2026 (March)